2013
DOI: 10.1097/pas.0b013e31828706c0
|View full text |Cite
|
Sign up to set email alerts
|

p16 Is Superior to ProEx C in Identifying High-grade Squamous Intraepithelial Lesions (HSIL) of the Anal Canal

Abstract: Although the incidence of human papillomavirus (HPV)-associated anal neoplasia is increasing, interobserver and intraobserver reproducibility in the grading of biopsy specimens from this area remains unacceptably low. Attempts to produce a more reproducible grading scheme have led to the use of biomarkers for the detection of high-risk HPV (HR-HPV). We evaluated the performance of standard morphology and biomarkers p16, ProEx C, and Ki-67 in a set of 75 lesions [17 nondysplastic lesions, 23 low-grade squamous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Past studies have also showed that HSIL is not always p16 positive; accordingly, p16 immunostaining should not be performed when the diagnosis of HSIL can be made on routine staining. 4,10,11 While a lack of p16 immunoreactivity is seen in most normal cells (which have p16 expression that is low at the mRNA and protein levels), in some cases, lack of p16 immunostaining could represent inactivation of the gene by deletion or methylation. 20,21 This study confirms the high degree of subjectivity involved in grading dysplasia in genital skin lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have also showed that HSIL is not always p16 positive; accordingly, p16 immunostaining should not be performed when the diagnosis of HSIL can be made on routine staining. 4,10,11 While a lack of p16 immunoreactivity is seen in most normal cells (which have p16 expression that is low at the mRNA and protein levels), in some cases, lack of p16 immunostaining could represent inactivation of the gene by deletion or methylation. 20,21 This study confirms the high degree of subjectivity involved in grading dysplasia in genital skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation for p16 immunostaining of equivocal lesions presumes an ultimate diagnosis of low‐grade squamous intraepithelial lesion (LSIL) for negative p16 staining and high‐grade squamous intraepithelial lesion (HSIL) for positive p16 staining in a case of ‐IN 2 . However, the role of p16 staining for aiding in evaluation of a wider spectrum of nonmucosal atypical genital skin lesions remains understudied . In order to narrow this knowledge gap, we sought to investigate the utility of p16 staining in the diagnosis of atypical genital skin lesions.…”
mentioning
confidence: 99%
“…4 p16 protein expression has been shown to be better than several other markers tested to date to confirm a diagnosis of HPV-related anal HSIL. 7,8,19 Several studies have shown that diffuse and strong nuclear or nuclear and cytoplasmic p16 expression strongly correlates with high-grade dysplasia, while focal or patchy nuclear staining may be seen in reactive epithelium and LSILs. 7 dysplasia), when there is diagnostic disagreement regarding the grade of dysplasia, or in samples that show changes that mimic true dysplasia (immature squamous metaplasia, sectioning artifact, atrophy, and reparative epithelial changes).…”
Section: Discussionmentioning
confidence: 98%
“…In histological specimens, especially on HRA‐obtained biopsies, p16 protein expression has been shown to be superior to all other markers tested to date, including Ki‐67 and ProEx‐C, to confirm a diagnosis of HPV‐related anal HSIL . The same indications and interpretation criteria can be applied in anal lesions as in cervical lesions.…”
Section: Precancerous Lesionsmentioning
confidence: 99%
“…In histological specimens, especially on HRAobtained biopsies, p16 protein expression has been shown to be superior to all other markers tested to date, including Ki-67 and ProEx-C, to confirm a diagnosis of HPV-related anal HSIL. [38][39][40] The same indications and interpretation criteria can be applied in anal lesions as in cervical lesions. A p16-positive result is defined as a strong and diffuse nuclear or nuclear-plus-cytoplasmic staining of the basal cell layers involving at least one-third of the epithelial thickness ( Figure 6).…”
Section: B I O M a R K E R Smentioning
confidence: 99%